Effects of acid hydrolysis on the structure, physicochemical properties and digestibility of starch-myristic acid complexes. (October 2019) - Sun, Shenglin; Hong, Yan; Gu, Zhengbiao; Cheng, Li; Li, Zhaofeng; Li, Caiming
Abstract: The effects of acid hydrolysis on the structure, physicochemical properties and in vitro digestibility of maize starch-myristic acid (MA) complexes were investigated. The complexing index (CI) of the complexes significantly decreased with increasing acid hydrolysis time. The native maize starch (MS)-MA complexes likely corresponded with the semi-crystalline type IIa, whereas the acid-hydrolyzed maize starch (AHM)-MA complexes mainly belonged to the less-ordered type I. The relative crystallinity in AHM-MA complexes was generally higher than that in MS-MA complexes. In addition, the MS and AHM could interact with MA to mainly form V6III complexes. The intermolecular interactions between starch and MA molecules were enhanced due to the formation of complexes. The transversal relaxation time in AHM 3 h-MA complexes was lower than that in other complexes. Moreover, the final viscosity of MS-MA, AHM 0.5 h-MA and AHM 1 h-MA complexes greatly increased. Besides, the MS-MA and AHM 0.5 h-MA complexes possessed higher G′ and G″ modulus than their counterparts. The MS-MA complexes had the highest resistant starch (RS) content (16.77%), whereas the AHM 3 h-MA complexes had the lowest RS content (5.03%). The present study could provide insights into the relationship among structure, physicochemical properties and digestibility of the complexes. Highlights: Acid hydrolysis treatment could hinder the formation of starch-myristic acid complex. The starch-myristic acid complexes mainly exhibited V6III polymorph structures. The complex type could be transformed from type IIa to type I after acid hydrolysis. Complexing index and viscoelasticity of complex affected resistant starch content. The molecular order of complexes was associated with physicochemical properties.